An Autocrine Cytokine/JAK/STAT-Signaling Induces Kynurenine Synthesis in Multidrug Resistant Human Cancer Cells - Campia, Ivana (PLoS One, 2015)
BACKGROUND: Multidrug resistant cancer cells are hard to eradicate for the inefficacy of conventional anticancer drugs. Besides escaping the cytotoxic effects of chemotherapy, they also bypass the pro-immunogenic effects induced by anticancer drugs: indeed they are not well recognized by host dendritic cells and do not elicit a durable anti-tumor immunity. It has not yet been investigated whether multidrug resistant cells have a different ability to induce immunosuppression than chemosensitive ones. We addressed this issue in human and murine chemosensitive and multidrug resistant cancer cells. RESULTS: We found that the activity and expression of indoleamine 2,3-dioxygenase 1 (IDO1), which catalyzes the conversion of tryptophan into the immunosuppressive metabolite kynurenine, was higher in all the multidrug resistant cells analyzed and that IDO1 inhibition reduced the growth of drug-resistant tumors in immunocompetent animals. In chemoresistant cells the basal activity of JAK1/STAT1 and JAK1/STAT3 signaling was higher, the STAT3 inhibitor PIAS3 was down-regulated, and the autocrine production of STAT3-target and IDO1-inducers cytokines IL-6, IL-4, IL-1β, IL-13, TNF-α and CD40L, was increased. The disruption of the JAK/STAT signaling lowered the IDO1 activity and reversed the kynurenine-induced pro-immunosuppressive effects, as revealed by the restored proliferation of T-lymphocytes in STAT-silenced chemoresistant cells. CONCLUSIONS: Our work shows that multidrug resistant cells have a stronger immunosuppressive attitude than chemosensitive cells, due to the constitutive activation of the JAK/STAT/IDO1 axis, thus resulting chemo- and immune-evasive. Disrupting this axis may significantly improve the efficacy of chemo-immunotherapy protocols against resistant tumors.